2012
DOI: 10.1002/tox.21761
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of pamam-coated gold nanoparticles in different unicellular models

Abstract: Polyamidoamine (PAMAM) dendrimers are used for many pharmaceutical and biomedical applications. However, the toxicological risks of several PAMAM-based compounds are still not fully evaluated, despite evidences of PAMAM deleterious effects on biological membranes, leading to toxicity. In this report, we investigated the toxicity of generation 0 PAMAM-coated gold nanoparticles (AuG0 NPs) in four different models to determine how different cellular systems are affected by PAMAM-coated NPs. Toxicity was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…The toxicity of AuNPs in C. reinhardtii was reported by Perreault et al (2011Perreault et al ( , 2012. The 24-h EC 10 and EC 50 values of AuNPs (2 nm) were 16 ± 17 and 83 ± 26 mg L À1 (Perreault et al, 2012). The reason that C. reinhardtii is insensitive to NPs may be because the cell wall functions as a barrier to NPs (Perreault et al, 2011).…”
Section: Characterization Of Aunpsmentioning
confidence: 88%
See 1 more Smart Citation
“…The toxicity of AuNPs in C. reinhardtii was reported by Perreault et al (2011Perreault et al ( , 2012. The 24-h EC 10 and EC 50 values of AuNPs (2 nm) were 16 ± 17 and 83 ± 26 mg L À1 (Perreault et al, 2012). The reason that C. reinhardtii is insensitive to NPs may be because the cell wall functions as a barrier to NPs (Perreault et al, 2011).…”
Section: Characterization Of Aunpsmentioning
confidence: 88%
“…C. reinhardtii growth was not inhibited by 50% at 10.11 mg L À1 , which was the highest exposure concentration tested in this study. The toxicity of AuNPs in C. reinhardtii was reported by Perreault et al (2011Perreault et al ( , 2012. The 24-h EC 10 and EC 50 values of AuNPs (2 nm) were 16 ± 17 and 83 ± 26 mg L À1 (Perreault et al, 2012).…”
Section: Characterization Of Aunpsmentioning
confidence: 90%
“…The growth of E. gracilis was significantly inhibited at Au-NP concentrations greater than 75 Â 10 10 particles/mL. Truong et al, 2012aTruong et al, , 2012bZhu et al, 2010), three waterflea species (Lee & Ranville, 2012;Li et al, 2010;Lovern et al, 2008), three mussel species (Tedesco et al, 2008(Tedesco et al, , 2010a(Tedesco et al, , 2010b, four algal species (Perreault et al, 2012a(Perreault et al, , 2012bRenault et al, 2008;Van Hoecke et al, 2013), and one bacterial species (Perreault et al, 2012b). Data from these earlier studies are shown in Supplementary Table S4.…”
Section: Data Compilationmentioning
confidence: 88%
“…Some of the available Au-NP toxicity datasets were excluded from the tabulated toxicity datasets. With the exception of Li et al (2010), Perreault et al (2012b) and Van Hoecke et al (2013), none of the published toxicity data for Au-NPs included available toxicity values (e.g. ECx, LCx, or NOEC).…”
Section: Data Evaluation and Tabulationmentioning
confidence: 98%
See 1 more Smart Citation